The imbalance of T helper 17/regulatory T cells and memory B cells during the early post-transplantation period in peripheral blood of living donor liver transplantation recipients under calcineurin inhibitor-based immunosuppression - Kim, Hee Yeon (Blackwell Science Inc, 2013)
There is limited clinical research regarding the changes in peripheral lymphocyte subsets during the early post-operative period of liver transplantation. Serial changes of T cells and B cells in living donor liver transplantation (LDLT) recipients during the early post-transplantion period were prospectively investigated. From June 2010 to February 2011, 27 consecutive LDLT recipients were enrolled. Percentages of T helper type 1 (Th1; interferon-γ-producing), Th2 (interleukin-4-producing), Th17 (interleukin-17-producing), regulatory T (Treg; CD4(+) CD25(+) FoxP3(+)), memory B (CD19(+) CD24(hi) CD38(−)) and mature B (CD19(+) CD24(int) CD38(int)) cells were measured using fluorescence-activated cell sorting. Patients were followed up for a median of 9·9 months (range 6·8−15·5 months) after transplantation. Serial monitoring of immunological profiles showed no significant suppression of Th1, Th2, Th17, mature B or memory B cells, whereas frequencies of Treg cells significantly decreased. Interleukin-17 production by central and effector memory cells was not suppressed during the early post-operative period. The continuous production of interleukin-17 by the memory T cells may contribute to the persistence of Th17 cells. This prospective study demonstrated that current immunosuppression maintained the effector T or memory B cells during the early post-transplantation period but significantly suppressed Treg cells. Serial immune monitoring may suggest clues for optimal or individualized immunosuppression during the early post-operative period in clinical practice.